Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/app11010436
|View full text |Cite
|
Sign up to set email alerts
|

Type and Amount of Legume Protein Concentrate Influencing the Technological, Nutritional, and Sensorial Properties of Wheat Bread

Abstract: Plant protein concentrates are used to enhance the nutritional quality of bread and to respond to the demand of consumers with respect to increased protein intake. In the present study, bread samples were produced using pea protein concentrate (PP) and soy protein concentrate (SP) substituting wheat flour by 5%, 10%, and 15%. The protein levels were between 1.2- and 1.7-fold (PP) and 1.1- and 1.3-fold (SP) higher than the control bread. The incorporation of 10% and 15% PP allowed for the achievement of a “high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Specialist attempts are made to balance the content of vitamins, minerals, and fibers lost through wheat refining without adding any chemical compound to the bakery products [5]. Moreover, an attempt is made to improve the quality of proteins in baked goods by adding various ingredients which contain essential amino acids that are deficient in wheat flour [6,7]. To correct these nutritional deficiencies, different grain flours can be used in bread making, such as legumes, oilseeds, pseudocereals, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specialist attempts are made to balance the content of vitamins, minerals, and fibers lost through wheat refining without adding any chemical compound to the bakery products [5]. Moreover, an attempt is made to improve the quality of proteins in baked goods by adding various ingredients which contain essential amino acids that are deficient in wheat flour [6,7]. To correct these nutritional deficiencies, different grain flours can be used in bread making, such as legumes, oilseeds, pseudocereals, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To correct these nutritional deficiencies, different grain flours can be used in bread making, such as legumes, oilseeds, pseudocereals, etc. [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Bread is the main source of vegetable protein, covering about 1/5-1/3 of the total protein requirement for the human body, but is deficient in essential amino acids, especially lysine, but also tryptophan and threonine. In order to correct this deficit, different ingredients may be used, such as legume protein concentrate as Belc et al [4] have reported in this Special Issue. Through refined wheat flour substitution with pea and soy protein concentrate up to 15% addition, the bread nutritional quality was improved.…”
mentioning
confidence: 99%
“…The quality of various bakery types have been reported in different ways in this Special Issue through baking loss, bread yield, bread volume, dallmann porosity, index of crumb, crumb moisture content [3], compositional analysis, loaf volume, crumb porosity, elasticity, colour parameters, texture properties, sensory ones through nose system, descriptive method [4], preferential method [2], free sugar content, total flavonoid content, total phenolic content, radical scavenging activity [8], carbohydrates, organic acids, folic acid, minerals [11], e.g., These methods are common ones used in the international literature to analyze bakery products quality from the nutritional and technological point of view. An innovative approach by using multivariate analysis as a statistical tool to evaluate bread quality in order to classified as a specific type of food product according to a standard database was reported in this Special Issue by Popescu et al [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation